Uporaba digitalnega modela višin in satelitskega posnetka RapidEye za zaznavanje kraških kotanj in brezstropih jam Podgorskega krasa - Grlj, Aleš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
Speleogenesis is the process of formation, development and disappearance of caves. The final stage in a cave development is called unroofed cave. The study of those features can help us understand karst landscape and karst phenomena. Since the unroofed caves are depressions on karst surface or just patches of non-karstic sediments with more vigorous vegetation, the study examines the possibility of their identification on the basis of morphometric characteristics and spectral properties of vegetation cover. The study is focused on a wider area of the Podgorski kras in southwestern Slovenia.
Keywords: digitalni model reliefa; geomorfologija; geomorphology; karst; kras (geologija); kraške jame; kraški pojavi; List of caves in Slovenia; nadmorska višina; Podgorski kras; relief; satelitski podatki; Slovenia; Slovenija; topography